PROJECT-BASED LEARNING AS A MEANS OF DEVELOPING STUDENTS’ CRITICAL THINKING IN THE COURSE «MULTIMEDIA TOOLS IN FOREIGN LANGUAGE EDUCATION» (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article examines the potential of project-based learning as an effective means of fostering critical thinking in pedagogical students studying the course "Multimedia in Foreign Language Teaching." It substantiates the importance of developing critical thinking as a core competency for future teachers, fostering analytical, reflective, and creative approaches to professional development in the context of digitalization of education. The author analyzes the course content, which is aimed at developing students' digital, methodological, and cognitive competencies through mastering multimedia technologies and completing educational projects. Particular attention is paid to the stages of organizing project-based learning, which contribute to the development of analytical, argumentative, decision-making, and self-assessment skills. The empirical part of the study presents the results of a student survey, confirming the effectiveness of project-based learning for developing critical thinking, digital literacy, and teamwork skills. It is concluded that integrating project-based learning into ICT-focused courses improves the quality of professional training for future teachers and facilitates their readiness to work in a digital educational environment.